2019
DOI: 10.1111/cei.13264
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pembrolizumab on CD4+CD25+, CD4+LAP+ and CD4+TIM-3+ T cell subsets

Abstract: Tumor immune evasion involves the expansion of avidly proliferating immunosuppressive cells and inhibition of effector T cell proliferation. Immune checkpoints (IC) block the activation pathways of tumor-reactive T cells. IC pathways are often exploited by tumor cells to evade immune destruction, and blocking these pathways through IC inhibitors (ICI) has shown promising results in multiple malignancies. In this study, we investigated the effects of an ICI, pembrolizumab, on various T cell subsets in vitro. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Studies have shown that there is an increase in the ratio of effector T cells to Tregs within the TME with IC blockade [4]. Of note, we have recently reported that CD4 + TIM-3 + T cells in circulation can promote proliferation of responder T cells, which was not affected by PD-1 blockade in vitro [36].…”
Section: Discussionmentioning
confidence: 73%
“…Studies have shown that there is an increase in the ratio of effector T cells to Tregs within the TME with IC blockade [4]. Of note, we have recently reported that CD4 + TIM-3 + T cells in circulation can promote proliferation of responder T cells, which was not affected by PD-1 blockade in vitro [36].…”
Section: Discussionmentioning
confidence: 73%
“…However, the effect of these inhibitors on Treg cells have not been clearly discriminated against its effect on T cells. A few reports including a study conducted by Toor et al (47, 48) suggest that PD-1 blockade does not modulate Treg cell phenotype or function, but instead targets activated T cells. A murine study conducted by Chen et al (49) demonstrates that PD-1 has no influence over the development and suppressive effects of thymically-derived Treg cells, however PD-1 appears to be crucial for differentiation of naïve CD4 + T cells into iTregs.…”
Section: Introduction—regulatory T Cell In Cancermentioning
confidence: 99%
“…CD8 is a maker of cytotoxic T lymphocytes [ 18 ], while TIM-3 indirectly suppresses effector T-cell activity by acting on myeloid-derived suppressor cells, Tregs, and dendritic cells [ 19 , 20 ]. We counted the number of positively stained cells at “hot spots” and found more positive cells near the tumor cells.…”
Section: Resultsmentioning
confidence: 99%